Perioperative inappropriate red blood cell transfusions significantly increase total costs in elective surgical patients, representing an important economic burden for hospitals - Saporito, Andrea; La Regina, Davide; Hofmann, Axel; Ruinelli, Lorenzo; Merler, Alessandro; Mongelli, Francesco; Trentino, Kevin M.; Ferrari, Paolo (Frontiers in Medicine, 2022)
Background Red blood cell (RBC) transfusions in surgical patients are associated to increased morbidity a hospital stay. However, little is known about how clinical and economic outcomes differ between appropriately and inappropriately transfused patients. We hypothesized that inappropriate RBC transfusions in elective surgical patients would significantly increase hospital cost. The aim of this study was to quantify the economic burden associated with inappropriate RBC transfusions. Methods We retrospectively included all adult patients admitted for elective non-cardiac surgery between January 2014 and March 2020. Patients were divided into three groups (not transfused, appropriately transfused and inappropriately transfused). The primary outcome was the excess in hospital cost in patients inappropriately transfused compared to non-transfused patients. Costs were calculated using a bottom-up approach and involving cost calculation on a granular level. According to international guidelines, transfusions were considered appropriate if administered with an ASA score of 1-2 and the last hemoglobin level measured before transfusion <70 g/L, or with an ASA score ≥3 and the last hemoglobin level <80 g/L. Cases where RBC transfusions were deemed necessary regardless of the Hb levels were reviewed by the patient blood management (PBM) board and classified accordingly. Secondary outcomes included total transfusion rate, transfusion index, and ALOS. Statistical analysis was carried out by multivariable regression models. Results During the study period there were 54,922 consecutive surgical admissions, of these 1,997 received an RBC transfusion, with 1,125 considered inappropriate. The adjusted cost of each inappropriate RBC transfusions was estimated in United States dollars (USD) 9,779 (95% CI, 9,358 - 10,199; p<0.001) and totaled USD 11,001,410 in our series. Inappropriately transfused patients had 1.6 times (95% CI, 1.5 to 1.6; p<0.001) longer ALOS (10.6 days vs 6.7 days) than non-transfused patients and a mean 2.35 RBC units per patient were administered. Conclusions Inappropriate RBC transfusions in elective surgical patients seem to be common and may represent a significant economic burden. In our experience, inappropriate transfusions significantly increased hospital costs by an average of USD 9,904 compared to non-transfused patients. Through specific PBM policy, hospitals may improve cost-effectiveness of their elective surgical activity by lowering inappropriate transfusions rate.